Lethal Agonistic Behavior Between Two Male Magellanic Woodpeckers Campephilus Magellanicus Observed in the Cape Horn Area - Vergara-Egert, P; Soto-Gonzalez, G; Moreira-Arce, D (Wilson Ornithological Society, 2016)
Agonistic behavior in woodpeckers has been described for a wide range of species, although previous studies have not reported aggressive encounters resulting in the death of adults. In this study, we provide the first evidence of lethal agonistic behavior between two male Magellanic Woodpeckers (Campephilus magellanicus) inhabiting Patagonia. This species is commonly regarded as the largest extant Campephilus woodpecker. The agonistic encounter was video recorded within the core territory of the dead individual and his mate, a previously banded and monitored pair, as part of a monitoring research on this species carried out during the last 2 years. A week after the fight, we recorded a non-banded young male Magellanic Woodpecker accompanying the dead individual s mate. This young male Magellanic Woodpecker is potentially the offspring of the former pair or perhaps a new mate replacing the dead individual. From this observation, we deduced that the previously occupied territory of the dead individual, as well as its breeding role, was subjected to reallocation by competing adjacent woodpecker families. This mortality event offers novel insight into the behavior of Magellanic Woodpeckers and suggests that lethal agonistic behavior likely could contribute to territory plasticity and family structure in this species. © 2016 The Wilson Ornithological Society.